Faktor Yang Berhubungan Dengan Kejadian Infeksi Saluran Pernapasan Akut (Ispa) Pada Balita Di Puskesmas Fatukanutu Kabupaten Kupang Nusa Tenggar Timur - Kartini Kartini (Journal of Health Quality Development, 2021)
Acute Respiratory Infection is an acute infection involving the upper respiratory tract organ and lower respiratory tract organ caused by virus, fungi and bactery which always increased on Province of East Nusa Tenggara Timur and ranked first in the top 10 desease in Puskesmas Fatukanutu. This research aimed to know the factors related with incidence of Acute respiratory Infection in the workspace of Puskesmas Fatukanutu District of Kupang. This research used a quantitative method with cross sectional study approach. Samples in this research as many as 86 who got from using purposive sampling techniques. Data collected by using questionnaires and observation sheets. Results of this research were analyzed by using chi square test and showed there was a relationship between smoking habit with incidence of acute respiratory infection on children under five years where the value of p = 0.032.There was no relationship between using firewood with incidence of acute respiratory infection on children under five years where the value of p = 0.535.There was a relationship between the type of floor with incidence of acute respiratory infection on children under five years where the value of p = 0.034. there was a relationship between ventilation with incidence of acute respiratory infection on children under five years where the value of p = 0.000. there was no a relationship between immunization status with incidence of acute respiratory infection on children under five years where the value of p = 0,148 and there was no a relationship between exclusive breastfeeding with incidence of acute respiratory infection on children under five years where the value of p = 0.227. It recommended that community should get more education or information to improve their knowledge about acute respiratory infection.